Determination Amylolitic Characteristic of Predominant Lactic Acid Bacteria Isolated during Growol Fermentation, in a Different Starch Medium Composition - Putri, Widya Dwi Rukmi; Zubaidah, Elok; Masahid, Ardiyan Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
In order to achieve efficient lactic acid production from starch, fermentation of avarious composition starch medium by lactic acid bacteriawas examined in this study. Many strains of Lactobacillus plantarum isolated from growol fermentation, Lactobacillus plantarumsubsp. plantarum NBRC 15891 and Lactobacillus amylophyllus NBRC 15881 were used as starter cultures in starch basis medium, i.e, basal, basal-starch, enriched basal-starch with polypeptone and yeast extract. Lactobacillus plantarum UA3, AA2, AA11 showed the highest cells growth compare to both reference strains, but Lactobacillus amylophyllus NBRC 15881 showed a greater ability to degrade starch indicated by decreasing of pH and starch content of the fermented substrate. Enriched medium with peptone and yeast extract could generate the growth and starch degradation capabilities for all types of lactic acid bacteria were used.